(untitled) (Journal of Paediatric Surgeons of Bangladesh, 2026)
Background: Background: Acute appendicitis is one of the most common causes of acute abdomen, which occurs in almost all age groups and especially in childhood. In many cases, the symptoms are atypical or equivocal and require laboratory investigations or imaging modalities to support or rule out the diagnosis. Objective: This study was conducted with an objective to assess the accuracy of neutrophil-lymphocyte ratio (NLR) and Paediatric Appendicitis Score (PAS) for discriminating simple and complicated appendicitis in children. Methods: This Cross-sectional analytic type study was conducted in Paediatric Surgery Department, Mymensingh Medical College Hospital from January, 2021 to June, 2023. Patients with appendicitis who admitted in the Paediatric surgery Department, Mymensingh Medical College Hospital were included according to inclusion criteria. After taking proper history, relevant investigations were done and peri-operative findings were observed and the resected appendix sent for histopathology. Recorded data were processed by computer and were presented by tables, diagrams and graphs based on data nature. The significance of this study was tested statistical ly by using sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV). Ethical permission was taken IRB from Mymensingh Medical College. Result: A total of 100 patients were enrolled in this study, most of the patients were in age group 6 to 10 years. Males (58%) were predominant than females (42%). PAS score was significantly higher in complicated appendicitis patients (7.31 ± 1.55) than simple appendicitis patients (5.24 ± 1.60) (p < 0.001). NLR was also higher in complicated appendicitis patients (5.12 ± 2.41) than simple appendicitis patients (4.24 ± 3.09), but the difference was not statistically significant (p = 0.112). The optimum cut-off levels for PAS is 5.5 with sensitivity of 86.3%, specificity of 65.3%, PPV of 72.1% and NPV of 82.1%. The area under the ROC curve was 0.822. The optimum cut-off levels for NLR is 3.87 with sensitivity of 76.5%, specificity of 71.4%, PPV of 73.6% and NPV of 74.5%. The area under the ROC curve was 0.728. Conclusion: According to the findings of the study, both PAS and NLR can be used to identify complicated appendicitis. PAS was more sensitive, while NLR was more specific. Journal of Paediatric Surgeons of Bangladesh (2022) Vol. 13 (1 & 2): 30-35